Um estudo sobre os principais fatores na implantação de sistemas ERP - Oliveira, Lindomar Subtil de (2006)
The implementation of Enterprise Resource Planning (ERP) system has become, in the last few decades, a reference of competitiveness to the business enterprise as a whole. The introduction of these systems has represented an important technological advancement, which brought more improvement and better results to the organizational performance, promoting more efficiency to the company and sustainability to its businesses. Nowadays, there are also other technologies, for instance, CRM, BI, EDI and Data Warehouse, which have been efficient supports aiming at better organizational results. The large utilization of ERP system has become scope of much discussion by specialists, researchers and professionals of the area, with the purpose of finding an answer for success and failure cases upon its implementation. Most of these related aspects contributed to originate the problem of this research, which intended to check “what are the main factors that influence on ERP system’s implementation?” Therefore, the main objective of this work was to present a study to identify which the main factors that help or difficult the ERP implementation processes are. Concerning the methodological procedures, this research used an inductive method characterized by an applied and exploratory research. On the data collection, firstly an appropriate bibliography survey about the subject was made, representing an indirect source. Regarding the direct source, a questionnaire was mailed to 50 large companies, besides the interview with two employees from a relevant company. The data results illustrated the factors concerning functional difficulties, identification and adjustment on business processes, as well as lack of support by ERP system on strategic plans, were other critical questions considered by the companies. In addition, the aspects regarding user’s technical qualification, training and engagement of the main leaders have also been evaluated as of great importance. However, it can be seen that behavioral aspects means the main critical factors that represent the success or failure on the system implementation. At the end of this research, suggestions are presented for new studies regarding the human influence on the system implementation, in order to evaluate the importance of involvement of different groups of people among the organization’s participants. Another suggestion that had been proposed is concerning the studies on the impacts of new information technologies utilization, considered as an extension ERP system application.